Ostriches and Obligations: Ethical Challenges Facing Research on Usual Care - Morain, Stephanie R. (The Hastings Center report, 2019)
In recent years, a robust body of scholarship has emerged that examines ethical challenges facing the learning health organization model. In “Bystander Ethics and Good Samaritanism,” James Sabin and colleagues make a valuable addition to this scholarship, identifying and exploring the important question of what researchers' obligations are to patients receiving “usual care” if “that care is seen as suboptimal.” The central issue that Sabin et al. faced was whether it would be acceptable for researchers to identify patients with untreated atrial fibrillation but then assign them to a control group that would not receive education about the importance of oral anticoagulation. The authors present this challenge as an issue of “bystander ethics.” To avoid being “bystanders” to identified instances of suboptimal care, the research team decided to instead identify a “delayed intervention” group for which they would not determine the members' anticoagulation status, thereby preventing them from knowing that specific patients met the criteria for oral anticoagulants but were not using them. This “workaround” approach strikes me as disingenuous.